Assessment of oak wood and bark contamination by 137Cs in the exclusion zone of the Chernobyl nuclear power plant - Garbaruk, Dmitriy; Uglyanets, Anatoliy (Journal of the Belarusian State University. Ecology, 2023)
The results of studying the 137Cs contamination of English oak (Quercus robur L.) trunks in high-aged oak forests in the most radioactive polluted part of the Polesye State Radiation-Ecological Reserve territory located in the evacuation (exclusion) zone of the Chernobyl nuclear power plant are presented. The features of modern surface contamination soil by 137Cs in oak forest stands have been established, the factors that caused them have been identified: removal of research objects from the release site and conditions for deposition of radioactive fallout, as well as vertical redistribution of radionuclide in the soil over the time since the accident. The density of 137Cs soil contamination varies by types of oak forest. The current indicators of 137Cs accumulation in wood, bark and oak trunks, their changes by forest types, the relationship with the density of soil pollution and the distance to the disaster site are determined. A 2–3-fold excess of 137Cs oak bark contamination was found in comparison with wood, which is due to their morpho-physiological characteristics. Over the past 25 years, the wood and bark proportions of the relative contributions to the specific activity of 137Cs of the oak trunks have changed significantly. The decrease in the contribution of the bark to the specific activity of 137Cs in the trunk is due to a slowdown in the entry of radionuclide into it. The 137Cs distribution in oak wood by classes of growth and development of trees by Craft is shown. It was found that the average values of the radionuclide specific activity in standing and lying deadwood are 25–28 % lower than in the wood of living trees. The tendency of decreasing of 137Cs concentration in oak wood from the periphery to the center of the trunk has been confirmed. As of 2021, according to the sanitary standard of the Republic of Belarus for the content of 137Cs 1480 Bq kg–1, harvesting of oak wood could be allowed in 84 % of the surveyed stands, oak trunks with bark – in 72 %. The standard of 740 Bq kg–1 corresponded to oak wood in bark and without bark in 32 % of forest stands.